Distribution and frequency of clinical criteria and rating scales for diagnosis and assessment of catatonia in different study types - Hirjak, Dusan; Brandt, Geva A.; Fritze, Stefan; Kubera, Katharina Maria; Northoff, Georg; Wolf, Robert Christian (Schizophrenia research, 2024)
Background - A comprehensive assessment of catatonic symptoms is decisive for diagnosis, neuronal correlates, and evaluation of treatment response and prognosis of catatonia. Studies conducted so far used different cut-off criteria and clinical rating scales to assess catatonia. Therefore, the main aim of this study was to examine the frequency and distribution of diagnostic criteria and clinical rating scales for assessing catatonia that were used in scientific studies so far. - Methods - We conducted a systematic review using PubMed searching for articles using catatonia rating scales/criteria published from January 1st 1952 (introduction of catatonic schizophrenia to first edition of the Diagnostic and Statistical Manual of Mental Disorders [DSM]) up to December 5th, 2022. - Results - 1928 articles were considered for analysis. 1762 (91,39 %) studies used one and 166 (8,61 %) used ≥2 definitions of catatonia. However, 979 (50,7 %) articles did not report any systematic assessment of catatonia. As for clinical criteria, DSM criteria were used by the majority of studies (n = 290; 14.0 %), followed by International Classification of Diseases (ICD) criteria (n = 61; 2.9 %). The Bush-Francis Catatonia Rating Scale (BFCRS) was found to be by far the most frequently utilized scale (n = 464; 22.4 % in the respective years), followed by Northoff Catatonia Rating Scale (NCRS) (n = 31; 1.5 % in the respective years). - Conclusion - DSM and ICD criteria as well as BFCRS and NCRS were most frequently utilized and can therefore be recommended as valid instruments for the assessment of catatonia symptomatology.